Pendampingan Kegiatan Pembelajaran Akidah Berbasis Game Open the Box Pada Santri TPA Al-Firdaus - Syahmidi, Syahmidi; A'ini, Nova Nur; Khasanah, Kusnia Nikmatul; Surawan, Surawan (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
Adherence learning at TPA Al-Firdaus still uses conventional methods that are less interesting for students. The low motivation of students encourages the need for technology-based innovation. This service aims to implement the Open the Box game as an interactive media to improve students' understanding of the ten angels of Allah, the pillars of faith, Islam, and thoyyibah sentences. This activity was carried out on February 17-20, 2025, at 15.30-16.30 WIB and was attended by 22 students. The method used is service learning, including preparation, delivery of material with songs and games, and interactive quiz-based evaluation. Evaluation data was collected through interactive quiz results and analyzed using the percentage formula of validity and practicality to measure the student's level of understanding. The evaluation results showed that 81.8% of students answered correctly. Based on the predetermined success criteria, the 81% score is included in the “Very Good” category, which shows that using the Open the Box game effectively increases santri understanding of the material of faith. This media increases santri's understanding, engagement, memory, and cognitive and social skills. Thus, the Open the Box game is effective as an innovation in akidah learning and can be applied in other non-formal education institutions.